Study of Nonsingular Fast Terminal Sliding-Mode Fault-Tolerant Control - Xu, Sendren Sheng-Dong; Chih-Chiang Chen; Zheng-Lun Wu (IEEE transactions on industrial electronics (1982), 2015)
This paper studies fault-tolerant control (FTC) designs based on nonsingular terminal sliding-mode control and nonsingular fast terminal sliding-mode control (NFTSMC). The proposed active FTC laws are shown to be able to achieve fault-tolerant objectives and maintain stabilization performance even when some of the actuators fail to operate. In comparison to existing sliding-mode control (SMC) fault-tolerant designs, the proposed schemes not only can retain the advantages of traditional SMC, including fast response, easy implementation, and robustness to disturbances/uncertainties, but also make the system states reach the control objective point in a finite amount of time. Moreover, they also resolve the potential singularity phenomena in traditional terminal and faster terminal SMC designs; meanwhile, the proposed NFTSMC fault-tolerant scheme also possesses the benefit of faster state convergence speed of NFTSMC. Finally, the proposed analytical results are also applied to the attitude control of a spacecraft. Simulation results demonstrate the benefits of the proposed schemes.